A lanthanide–mercury compound: preparation and photophysical properties. Issue 1 (1st February 2021) - Chen, Wen-Tong
Abstract : A neodymium (Nd)–mercury (Hg) complex [Nd(IA)2 (H2 O)3 (NO3 )(HgCl2 )] n ·2 n H2 O· n EtOH (1 ; IA is isonicotinic acid anion) was synthesised and characterised. Compound 1 is of monoclinic system, space group C 2/ c with a = 25.4224(12), b = 8.1410(3), c = 22.2963(9) Å, β = 90.788(4)°, V = 4614.1(3) Å 3, C14 H24 Cl2 HgN3 NdO13, Z = 8, M r = 858.09, D c = 2.471 g/cm 3, S = 1.120, μ (Mo Kα ) = 9.174 mm −1, F (000) = 3256, R = 0.0530 and wR = 0.1288. The mercury (II) (Hg 2+ ) ions are bound by two terminal chloride (Cl − ) ions and two nitrogen (N) atoms, displaying a distorted tetrahedral geometry. The neodymium (III) (Nd 3+ ) ion is coordinated with nine oxygen (O) atoms to form a monocapped square antiprismatic polyhedron. Every two neighbouring neodymium (III) ions are interlinked by two μ 3 -bridging IA groups to form a one-dimensional (1D) infinite –Nd–IA2 –Nd– chain. The 1D chains link to each other through HgCl2 N2 tetrahedra and yield a two-dimensional layer. It emits cyan photoluminescence, which should be due to the 4 G 11/2 → 4 I 9/2 transition of the 4f electrons of the neodymium ions. It exhibits Commission Internationale de l'Éclairage chromaticity coordinates of (0.1274, 0.3525). A solid-state diffuse reflectance spectrum unveils that it has a 2.51 eV band gap.